Etnomatematika dalam Proses Pembuatan Pom-Pom Sagu: Kajian Budaya dan Matematika di Desa Tabarfane, Kabupaten Kepulauan Aru: Etnomatematika Dalam Proses Pembuatan Pom-Pom Sagu: Kajian Budaya Dan Matematika Di Desa Tabarfane, Kabupaten Kepulauan Aru - Temarwut Djamiri, Amalia; Lessy, Djaffar; Sopamena, Patma; Rahman, Abdillah (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2026)
This study aims to describe and analyze the mathematical concepts embedded in the traditional production of sago pom-pom in Tabarfane Village, Aru Islands Regency. Using a qualitative approach with an interpretive ethnographic design, data were gathered through direct observation, in-depth interviews with pom-pom producers, and field documentation. Findings reveal that each stage of production—washing, drying, sifting, burning, cooling, cutting, sun-drying, and packaging—naturally embodies mathematical activities as categorized by Bishop: counting, measuring, locating, designing, explaining, and playing. These activities involve geometric concepts such as cylinders, circles, and triangular prisms, alongside basic arithmetic operations and equivalent fractions, all practiced intuitively within a framework of local wisdom. These findings affirm that ethnomathematics present in sago pom-pom production not only contributes to cultural preservation but also holds strategic value as a contextual learning resource in mathematics education